Sustainable solar housing - Hastings, Robert, 1945-; Wall, Maria (Earthscan, 2007)
Annotation This far-reaching and authoritative two-volume set examines a range of potential solutions for low-energy building design, considering different strategies (energy conservation and renewable energy) and technologies (relating to the building envelope, ventilation, heat delivery, heat production, heat storage, electricity and control). Energy and life-cycle impacts are considered as crucial factors, including passive and active solar use, daylighting and high efficiency conventional heat production. Each volume assesses the potential of these options in a variety of contexts, covering different housing types (apartment, row and detached) in cold, temperate and mild climates. The impressive list of expert authors from 14 countries includes a mix of internationally respected academics and practitioners, working together within the framework of a five-year International Energy Agency (IEA) research project.Volume 1 presents strategies and solutions, offering the reader a solid basis for developing concepts, considering environmental and economic concerns for housing projects in a variety of contexts.Volume 2 offers a detailed analysis of exemplary buildings in different European countries and examines the various technologies employed to achieve their remarkable performance. Aided by clear, full colour illustrations, it offers invaluable insights into the application of these technologies.
"Published by Earthscan on behalf of the International Energy Agency (IEA), Solar Heating & Cooling Programme (SHC) and Energy Conservation in Buildings and Community Systems Programme (ECBCS)"--T.p. verso.
Keywords: Solar houses -- Design and construction.; Solar houses -- Europe -- Design and construction -- Case studies.; Dwellings -- Energy conservation.; Europe.; elektronické knihy; electronic books